2015
DOI: 10.1088/0256-307x/32/9/092501
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Perfect Fluidity and Jet Quenching in Semi-Quark-Gluon Monopole Plasmas

Abstract: We utilize a new framework, CUJET3.0, to deduce the energy and temperature dependence of jet transport parameter,q(E > 10 GeV, T ), from a combined analysis of available data on nuclear modification factor and azimuthal asymmetries from RHIC/BNL and LHC/CERN on high energy nuclear collisions. Extending a previous perturbative-QCD based jet energy loss model (known as CUJET2.0) with (2+1)D viscous hydrodynamic bulk evolution, this new framework includes three novel features of nonperturbative physics origin: (1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
154
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(165 citation statements)
references
References 92 publications
(173 reference statements)
10
154
1
Order By: Relevance
“…It's quite convenient to use the holographic method based on the AdS/CFT correspondence to study the dynamical properties, while Lattice calculation in this area still suffer large uncertainty. Within holographic framework, our previous work [65] do show that near the transition point there would be nontrivial enhancement ofq/T 3 , which is closely related to the phase transition and is consistent with the phenomenological studies in [66][67][68].…”
Section: Jhep06(2015)046supporting
confidence: 87%
See 1 more Smart Citation
“…It's quite convenient to use the holographic method based on the AdS/CFT correspondence to study the dynamical properties, while Lattice calculation in this area still suffer large uncertainty. Within holographic framework, our previous work [65] do show that near the transition point there would be nontrivial enhancement ofq/T 3 , which is closely related to the phase transition and is consistent with the phenomenological studies in [66][67][68].…”
Section: Jhep06(2015)046supporting
confidence: 87%
“…The location of valley is almost same as the location of the peak position inq/T 3 and the peak of the trace anomaly as well as the peak of the bulk viscosity. This opposite trends of η/s andq/T 3 near T c is also observed in phenomenological study [68].…”
Section: Shear Viscosity With Higher Derivative Correctionssupporting
confidence: 69%
“…[36,37]) to obtain a simultaneous description of R AA (p T ) and high p T elliptic flow. Model calculations typically give a small v hard 2 (p T ) that is incompatible with elliptic flow data.…”
mentioning
confidence: 99%
“…This effect has been discussed in literature [5,12,13] and recently it has been suggested by CUJET3.0 [14] that a temperature and energydependent jet-medium coupling κ = κ(E 2 , T ), which includes non-perturbative effects around the phase transition of T c ∼ 160 MeV, can overcome this problem.…”
Section: Resultsmentioning
confidence: 96%
“…R AA and v 2 requires a jet-medium coupling that depends on the energy of the jet, the temperature of the medium [5,14], and non-equilibrium effects around the phase transition. We also contrasted a hydrodynamic background (VISH2+1) [6] with a medium obtained from the parton cascade BAMPS [7] and showed that the influence of the underlying bulk medium considered is suprisingly small.…”
mentioning
confidence: 99%